PENGARUH CITRA DESTINASI, FASILITAS WISATA DAN EXPERIENTIAL MARKETING TERHADAP LOYALITAS MELALUI KEPUASAN (STUDI PADA PENGUNJUNG DOMESTIK TAMAN WISATA CANDI BOROBUDUR) - Ratna Acintya Putri; Naili Farida; Reni Shinta Dewi (Jurnal Ilmu Administrasi Bisnis, 2015)
This study is based on the tourism phenomenon developed into a worldwide industry and the developing business industry. The developing tourism business industry creates high competition among tourism destinations. The organizers of tourism destinations are competing to increase the number of tourist visitors. Borobudur Temple Tourism which is the main tourist destination of Central Java, especially Magelang Regency, is prioritized to gain more visitors. However since 2009 until 2012 there was a fluctuation in decline of domestic tourist visitors. The purpose of this research is to find out the influence of destination image, tourism facilities and experiential marketing towards loyalty through satisfaction in Borobudur Temple Tourism. The type of this research is explanatory research, with data collecting technique by questionnaire and interview. The sampling technique of this research use purposive sampling. The sample in this research were 100 respondents who were Borobudur temple’s domestic tourists. This research is uses qualitative and quantitative analysis technique. Quantitative analysis use validity test, reliability test, correlation coefficient, simple and multiple regression analysis, the coefficient of determination, a signification test (t test and F test) and path analysis.The result of this research approved that destination image (X1), tourism facilities (X2), and experiential marketing (X3) partially or simultaneously can influenced visitors’ satisfaction (Y1) and visitors’ loyalty (Y2). According the result of path analysis showed that visitors’ satisfaction variable is not intervening variable towards visitors’ loyalty in this research.